Curcumin inhibits influenza virus infection and haemagglutination activity - Chen, Da-Yuan; Shien, Jui-Hung; Tiley, Laurence; Chiou, Shyan-Song; Wang, Sheng-Yang; Chang, Tien-Jye; Lee, Ya-Jane; Chan, Kun-Wei; Hsu, Wei-Li (Food chemistry, 2010)
Curcumin (diferuloylmethane) is a widely used spice and colouring agent in food. Accumulated evidence indicates that curcumin is associated with a great variety of pharmacological activities, including an anti-microbial effect. In this study, the anti-influenza activity of curcumin was evaluated. Our results demonstrated that treatment with 30 μM curcumin reduced the yield of virus by over 90% in cell culture. The EC 50 determined using plaque reduction assays was approximately 0.47 μM (with a selective index of 92.5). Time of drug addition experiments demonstrated curcumin had a direct effect on viral particle infectivity that was reflected by the inhibition of haemagglutination; this effect was observed in H1N1 as well as in H6N1 subtype. In contrast to amantadine, viruses did not develop resistance to curcumin. Furthermore, by comparison of the antiviral activity of structural analogues, the methoxyl groups of curcumin do not play a significant role in the haemagglutinin interaction.